Presentation of noise during acute restraint stress attenuates expression of immediate early genes and arginine vasopressin in the hypothalamic paraventricular nucleus but not corticosterone secretion in rats. (July 2015) - Sugimoto, Koji; Ohmomo, Hideki; Shutoh, Fumihiro; Nogami, Haruo; Hisano, Setsuji
Highlights: Restraint stress induced c-Fos and JunB expression in paraventricular nucleus (PVN). White and pink noise attenuated c-Fos and JunB expression in the parvicellular PVN. Stress-evoked high plasma CORT level was unchanged by acoustic stimuli. Stress-induced AVP hnRNA expression was attenuated by white noise. JunB co-localized with c-Fos or AVP hnRNA in the parvicellular PVN. Abstract: The present study investigated the effect of acoustic stimulation on the activation of the hypothalamic-pituitary-adrenal (HPA) axis in rats submitted to acute restraint stress, through semi-quantitative histochemical analysis of expression of immediate early gene products (c-Fos, JunB and phosphorylated c-Jun) and arginine vasopressin (AVP) hnRNA in the paraventricular nucleus (PVN). Simultaneous presentation of white or pink noise with restraint resulted in a significant attenuation of stress-induced c-Fos and JunB expression in the dorsal body of dorsal medial parvicellular subdivision (mpdd) of the PVN, as compared with restraint without noise. However, this presentation did not change phosphorylation of c-Jun and the plasma corticosterone level. Moreover, white noise presentation during restraint led to a reduction in the number of c-Fos- or JunB-expressing corticotropin-releasing hormone (CRH) neurons and the number of neurons expressing AVP hnRNA in the mpdd. Dual-histochemical labeling revealed co-expression of c-Fos and JunB, as well as JunB and AVP hnRNA in mpdd neurons. These data suggest that acoustic stimuli have an attenuation effect on the restraint-induced activation of neuroendocrine CRH neurons, resulting in the reduction in AVP production as an adaptation of HPA axis to repeated stress.